LEGAL ANALYSIS OF THE IMPLEMENTATION OF PKWT FOR BANYUWANGI MARITIME ACADEMY CADETS (AKABA) IN THE IMPLEMENTATION OF EID HOMECOMING TRANSPORTATION AT KETAPANG PORT, BANYUWANGI - GILIMANUK, BALI - Janoko Janoko; Saiful Rohman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Sea transportation plays a strategic role in supporting mobility in Indonesia, especially during the Lebaran homecoming period, which is marked by a significant increase in passenger and vehicle flows. The Ketapang–Gilimanuk crossing route is one of the busiest corridors during this period. To support operational services, maritime cadets from institutions such as Akademi Kelautan Banyuwangi (AKABA) are often involved. Their participation can be carried out through a fixed-term employment agreement (Perjanjian Kerja Waktu Tertentu / PKWT), as regulated in Indonesian labor law. This study aims to analyze the legal implementation of PKWT for AKABA cadets in Lebaran transportation operations and to examine the forms of legal protection provided. The research uses a normative legal method with statutory and conceptual approaches. The results show that the application of PKWT for cadets is legally permissible as long as it complies with regulations, particularly for temporary or seasonal work. However, its implementation must also ensure legal protection, work safety, and clarity of employment status to prevent violations of cadets’ rights as both workers and students. Therefore, clearer regulations and stronger coordination between educational institutions, transport operators, and related stakeholders are needed to ensure legal certainty and protection for cadets involved in Lebaran transportation activities.